InCVAX – A novel strategy for treatment of late-stage, metastatic cancers through photoimmunotherapy induced tumor-specific immunity. Issue 2 (10th April 2015) - Zhou, Feifan; Li, Xiaosong; Naylor, Mark F.; Hode, Tomas; Nordquist, Robert E.; Alleruzzo, Luciano; Raker, Joseph; Lam, Samuel S.K.; Du, Nan; Shi, Lei; Wang, Xiuli; Chen, Wei R.
Highlights: Laser immunotherapy (LIT) is a novel cancer treatment strategy that uses local photothermal irradiation and a local immunological stimulation. A novel immunoadjuvant, glycated chitosan (GC), was developed to work with laser interaction to creates an in situ autologous cancer vaccine (inCVAX). Furthermore, inCVAX has been administered in initial clinical trials for the treatment of patients with metastatic breast cancer with promising outcomes. Abstract: A novel, promising potential cancer vaccine strategy was proposed to use a two-injection procedure for solid tumors to prompt the immune system to identify and systemically eliminate primary and metastatic cancers. The two-injection procedure consists of local photothermal application on a selected tumor intended to liberate whole cell tumor antigens, followed by a local injection of an immunoadjuvant that consists of a semi-synthetic functionalized glucosamine polymer, N -dihydro-galacto-chitosan (GC), which is intended to activate antigen presenting cells and facilitate an increased uptake of tumor antigens. This strategy is thus proposed as an in situ autologous cancer vaccine (inCVAX) that may activate antigen presenting cells and expose them to tumor antigens in situ, with the intention of inducing a systemic tumor specific T-cell response. Here, the development of inCVAX for the treatment of metastatic cancers in the past decades is systematically reviewed. The antitumor immune responses of local photothermal treatment and immunological stimulation with GC are also discussed. This treatment approach is also commonly referred to as laser immunotherapy (LIT).